Determination of Lime Requirement with Compost on Acidic Ultisols for Wheat Crop in the Gurage Zone of Ethiopia - Dereje Dejene; Teshome Yitbarek; Abdeta Jembere (Applied and Environmental Soil Science)
Acidic soil adversely affects the plant growth and production. Various ameliorating strategies are known, but the optimum rate of lime and compost rate determination for better nutrient management and production in acid Ultisols was not well studied, so the main objective of this study was to determine optimum lime and compost rate for wheat production. A pot experiment was performed on the soil collected from Yefereze (Cheha District). The incubation trail was conducted in factorial combination of four level lime (8.44, 6.33, 4.22, and 0 t·ha−1) and compost (15, 10, 5, and 0 t·ha−1). The sixteen treatments were arranged in completed randomized design (CRD) with triplicate replications in the greenhouse. After 75 days, each pot that was planted with wheat and crop performance had been monitored. The textural class of the soils of the experiment was clay with strongly acidic pH. The organic carbon (2.17%) and total nitrogen content (0.17%) status was medium. The available phosphorus (Av. P) contents were very low (1.63 ppm). The experimental study result revealed that all the three rates of lime and compost continuously improve the soil pH throughout the study periods and the maximum soil pH (6.53) was obtained in combination of 8.44 t·ha−1 and 10 t·ha−1 lime and compost, respectively. The compost amended treatment indicated slight improvement in soil reaction which assert that using compost alone did not reduce soil acidity within 75-day periods in strongly acidic soil condition for suitable wheat production. Liming alone or integrated application increases soil pH (4.69 to 6.53), cation exchangeable capacity (CEC) (27.18 to 31.58 cmolckg−1), exchangeable calcium (3.56 to 8.43 cmolckg−1), available phosphorus (Av.P) (1.63 to 5.27 ppm), total nitrogen (TN) (0.19 to 0.24 ppm), and exchangeable acidity reduced (0.73 cmolckg−1 to trace). Integrated application of 8.44 and 5 t·ha−1 lime and compost rates improve the overall soil property and maximize the wheat yield by 24.26%. Generally, the limiting factor for wheat production of the study area was the acidity of the soil. The combined application of lime and compost raised the pH and improved the suitability of the soil for wheat production. However, the status of Av. P was low after the amendment, and it is advisable to integrate phosphorus containing fertilizer in addition to lime and compost for optimum and sustainable production of wheat in the study area. Since the incubation and greenhouse experiment were conducted in a controlled environment, there is a need for field verification. It is also advisable to assess the economic feasibility of the different rates of lime and compost for an appropriate soil management decision.